2013
DOI: 10.1007/s00709-013-0540-9
|View full text |Cite
|
Sign up to set email alerts
|

Co-expression of the Arabidopsis SOS genes enhances salt tolerance in transgenic tall fescue (Festuca arundinacea Schreb.)

Abstract: Crop productivity is greatly affected by soil salinity; therefore, improvement in salinity tolerance of crops is a major goal in salt-tolerant breeding. The Salt Overly Sensitive (SOS) signal-transduction pathway plays a key role in ion homeostasis and salt tolerance in plants. Here, we report that overexpression of Arabidopsis thaliana SOS1+SOS2+SOS3 genes enhanced salt tolerance in tall fescue. The transgenic plants displayed superior growth and accumulated less Na+ and more K+ in roots after 350 mM NaCl tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(55 citation statements)
references
References 60 publications
1
49
0
Order By: Relevance
“…It is widely used for general purpose turf and lowHandling Editor: Peter Nick Electronic supplementary material The online version of this article (doi:10.1007/s00709-014-0748-3) contains supplementary material, which is available to authorized users. maintenance grass cover and plays an important role in environmental protection and livestock production (Wang and Ge 2005;Ma et al 2014). Accordingly, an increased tolerance to unfavorable environmental conditions such as drought, high soil salinity, extreme temperature, ultraviolet-B radiation, high light, air pollution, heavy metals, or combination of these conditions appears indispensable for tall fescue growth and development (Zsigmond et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is widely used for general purpose turf and lowHandling Editor: Peter Nick Electronic supplementary material The online version of this article (doi:10.1007/s00709-014-0748-3) contains supplementary material, which is available to authorized users. maintenance grass cover and plays an important role in environmental protection and livestock production (Wang and Ge 2005;Ma et al 2014). Accordingly, an increased tolerance to unfavorable environmental conditions such as drought, high soil salinity, extreme temperature, ultraviolet-B radiation, high light, air pollution, heavy metals, or combination of these conditions appears indispensable for tall fescue growth and development (Zsigmond et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In preliminary studies, it could be overcome through traditional plant breeding or producing transgenic plants, but these biotechnological methods applied to develop salt-resistant plants or improve salt-tolerance of crops were not much successful, even after gene improvement (Dionisio-sese and Tobita 2000; Ottow et al 2005;Bing et al 2013;Ma et al 2014). Then the use of some physical methods with low cost and low risk like He-Ne laser radiation for protecting plant cells against oxidative damage and enhancing plants salt tolerance could be the attractive solution to overcome the salinity problem.…”
Section: Introductionmentioning
confidence: 99%
“…In the study, we used the leaf and stem-specific ST-LS1 promoter to make no cry3A gene expression in stems and tubers, which seems to be more favorable to the transgenic biosafety for food. Up to now, the transgenic crops have widely appeared in many countries, and many insect-resistant strains, such as rice, cotton, creeping bentgrass, tall fescue, Arabidopsis and Brachypodium distachyon have been planted in the laboratory and in greenhouses [48][49][50][51][52][53][54]. In this study, the results from inoculation with first-instar larvae on plants showed that larvae in some transgenic lines led to higher mortality, lower insect biomass accumulation and foliage consumption.…”
Section: Discussionmentioning
confidence: 89%
“…Intracellular Cd 2+ concentrations in leaves and roots of seedlings were analyzed by atomic absorption spectrometer (AAS, S2, USA, Thermo) (Ma et al 2014). The oven-dried leaves and roots (5.0 g respectively, in an oven at 80°C) were collected, and then digested with HNO 3 overnight prior to further determination.…”
Section: Cdsnps Distribution and CD 2+ Accumulation In Plant Tissuementioning
confidence: 99%
“…is the predominant, perennial, open-pollinated, cool-season turf and forage grass species grown or planted under diverse environmental conditions (Dong et al 2007;Xu et al 2010Xu et al , 2013. It is widely used for general purpose turf and low-maintenance grass cover, and plays an important role in environmental protection and livestock production in China (Wang and Ge 2005;Ma et al 2014). Accordingly, increased tolerance to unfavorable environmental conditions such as drought, high soil salinity, extreme temperature, ultraviolet-B radiation, high light, air pollution, heavy metals, NPs or some combination of these conditions appears indispensable for tall fescue growth and development (Yang et al 2012b;Zsigmond et al 2012;Qiu et al 2013;Gao et al 2015;Hu et al 2015;Gao et al 2016).…”
Section: Introductionmentioning
confidence: 99%